2005
DOI: 10.1111/j.1540-8167.2005.50192.x
|View full text |Cite
|
Sign up to set email alerts
|

Left Mitral Isthmus Ablation Associated with PV Isolation: Long‐Term Results of a Prospective Randomized Study

Abstract: The addition of mitral isthmus line to the PV disconnection allows a significant improvement of sinus rhythm maintenance rate, particularly in patients with persistent AF, without the risk for major complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
215
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 205 publications
(228 citation statements)
references
References 27 publications
11
215
2
Order By: Relevance
“…5,8,10 Furthermore, additional linear ablation demonstrated better clinical outcomes in another 3 randomized trials. 6,7,12 Nonetheless, results of other trials did not show a clinical benefit of additional CFAE ablation, 4,9 and the recently published STAR AF II trial revealed no difference in clinical outcomes when comparing stand-alone PVI to PVI plus additional CFAE or linear ablation in a large cohort of patients with persistent AF. 13 The stepwise ablation approach was first investigated by Haïssaguerre et al 15 and consisted of the sequential combination of PVI and additional ablation of CFAEs and, in case of conversion to AT during the ablation procedure, linear ablation; in that original study, 95% of patients were in SR after 1 year and multiple ablation procedures.…”
Section: Current Ablation Strategies For Chronic Afmentioning
confidence: 90%
See 2 more Smart Citations
“…5,8,10 Furthermore, additional linear ablation demonstrated better clinical outcomes in another 3 randomized trials. 6,7,12 Nonetheless, results of other trials did not show a clinical benefit of additional CFAE ablation, 4,9 and the recently published STAR AF II trial revealed no difference in clinical outcomes when comparing stand-alone PVI to PVI plus additional CFAE or linear ablation in a large cohort of patients with persistent AF. 13 The stepwise ablation approach was first investigated by Haïssaguerre et al 15 and consisted of the sequential combination of PVI and additional ablation of CFAEs and, in case of conversion to AT during the ablation procedure, linear ablation; in that original study, 95% of patients were in SR after 1 year and multiple ablation procedures.…”
Section: Current Ablation Strategies For Chronic Afmentioning
confidence: 90%
“…Six (5%) of the 124 patients withdrew their consent during follow-up and were excluded from the study, resulting in a total of 118 Duration of AF, mo 12 [7,24] 12 [7,24] 12 [7,24] Type of AF Persistent 69 (59) 35 (57) 34 (60) Long-standing persistent 49 (42) 26 (43) 23 (40) CAD 11 (9) 5 (8) 6 (11) Valvular disease 14 (12) 8 (13) 6 (11) Hypertension 64 (54) 35 (57) 29 (51) Diabetes mellitus 9 (8) 5 (8) 4 (7) CHADS 2 score (87) 52 (85) 51 (90) 2-3 14 (12) 8 (13) 6 (11) Values are mean±SD, median [first quartile, third quartile], or n (%). AF indicates atrial fibrillation; BMI, body mass index; CAD, coronary artery disease; CHADS 2 , stroke risk score based on congestive heart failure, hypertension, age ≥75 years, diabetes mellitus, prior stroke/transient ischemic attack/thromboembolism; CHA 2 DS 2 -VASc, stroke risk score based on congestive heart failure, hypertension, age ≥75 years, diabetes mellitus, prior stroke/ transient ischemic attack/thromboembolism, vascular disease, age 65-74 years, sex; LA, left atrium; and LVEF, left ventricular ejection fraction.…”
Section: Patientsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, when the same approaches are applied to persistent or long-standing persistent AF patients, the clinical success has been limited 2,3 and has led to the search for the ideal ablation strategy. The vast contrast in success suggests that the mechanisms underlying the maintenance of persistent AF are different to their paroxysmal counterparts.…”
Section: Introductionmentioning
confidence: 99%
“…1,2,18) However, left mitral isthmus ablation, left atrial roof linear ablation, and linear catheter ablation to transect the anterior left atrium were shown to be necessary to maintain sinus rhythm particularly in patients with persistent AF. [19][20][21] Furthermore, in patients with persistent and permanent AF, circumferential PV ablation, combined with linear lesions in the right atrium in addition to left atrial and CS ablation, is reported to be feasible and safe, with a significantly high success rate. 22,23) However, creating transmural linear lesions with a multipolar ablation system or by the pull-back approach is difficult.…”
Section: Discussionmentioning
confidence: 99%